Influence of local fatigue damage evolution on crack initiation behavior in a friction stir welded Al-Mg-Sc alloy. (June 2017) - Besel, Yasuko; Besel, Michael; Alfaro Mercado, Ulises; Kakiuchi, Toshifumi; Hirata, Taiki; Uematsu, Yoshihiko
Highlights: Local strain evolution under fatigue loading was investigated in a FSWed Al alloy. Non-uniform local plastic straining was observed even in the stir zone. Degree of local plastic strain was consistent with thermo-mechanical conditions. Fatigue crack initiation behavior was affected by the local plastic strain. Abstract: Axial loading fatigue tests were carried out in a friction stir welded Al-Mg-Sc alloy. Local strain evolution under fatigue loading was monitored using small strain gages. The weld joint had very complex heterogeneous microstructure and hardness distributions. The cyclic stress-strain responses were strongly dependent on the local hardness distribution. The cyclic plastic strain was observed intensively on the advancing side in the soft stir zone. Transgranular fatigue cracks initiated in the stir zone on the top surface, where high plastic strain was observed. To the contrary, intergranular crack initiations were observed on the bottom surface. The crack initiation was caused mainly by the cyclic plastic straining on the top side. However on the bottom side, the residual initial oxide layer, which was not sufficiently stirred, as well as the local cyclic plastic straining could be attributed to the intergranular crack initiations.